PENERAPAN MODEL KWEKA DAN MORISSEY DALAM MENERANGKAN PERTUMBUHAN EKONOMI DI JAWA TENGAH - Sri Isnowati (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2012)
This research aims to analyze the Kweka and Morissey Model in explaining the economic growth in CentralJava province. The Kweka and Morissey Model shows variables influencing the economic growth are privatesektor investment, government investment, government expenses, labour and economic openness. This researchemployed secondary data published by Biro Pusat Statistik (Statistic Centre Bureau) and Bank Indonesia(Indonesian Bank). They were annual data from 1985 to 2009. This research used Ordinary Least Square (OLS)regression with Error Correction Model (ECM) approach. The selection of ECM model was due to its capabilityto explain short term and long term phenomena. The result showed that variable of private sektor investmentinfluent positively and significantly in both short and long term. Government investment variable influentsignificantly in both short and long term and its influence towards economic growth was positive. Governmentexpenditure variable investment influent positively and significantly in both short and long term. Meanwhile,labor variable investment influents positively in the long term but it did not influents significantly in both shortand long term. For economic openness variable the value of coefficient regression of short and long term waspositive and significant.Key words: economic growth, private sektor investment, government investment, government expenditure,labour